Dostoevsky’s influence on Emmanuel Levinas’ philosophy - Medina Delgadillo, Jorge (Acta Universitaria, 2014)
Prior to his philosophical and Talmudic studies outside of Lithuania, the main source of Emmanuel Levinas’ intellectual training was provided by the Kovno yeshiva and an avid reading of Russian literature. We contend that the influence of Dostoevsky, particularly, and later reinforced by Grossman, manifests its effect on Levinas’ ethics of excess as well as in many of his key starting points, such as the asymmetry of inter-subjectivity, immemorial past, and Messianic responsibility, therefore we can say that Levinas’ ethical proposal cannot be fully understood without the theological literature of Dostoevsky.
Keywords: Array; Array; Array; Array; Array